The nuclear stellar cluster in NGC 1068 - Thatte, N; Genzel, R; Tacconi, L; Krabbe, A; Kroker, H (1997)
We have imaged a compact stellar cluster, with a characteristic size of 50 pc, toward the nucleus of NGC 1068, using near IR imaging spectroscopy of stellar absorption features in the H and K bands. The near IR stellar light is attributed to a population of late type stars, with an average spectral type of M0. Based on light-to-mass ratio measurements, we derive an upper limit for the age of the nuclear cluster of 4 x 10(9) years. The stellar cluster contributes a non-negligible fraction of the total nuclear bolometric luminosity, a value of 5% being a very conservative lower limit. The compact stellar distribution identifies the dynamical center of the galaxy as being coincident with the peak of the It band emission. The morphology of the excited molecular gas, revealed by mapping the H-2 S(1) line at 2.12 mu m, shows a molecular ring with a radius of similar to 100 pc. Millimeter interferometric imaging in the CO J = 2 --> 1 transition at 1.3 mm shows the ring to be rotating with velocities of similar to 100 km s(-1).